2021
DOI: 10.46656/access.2021.2.1(2)
|View full text |Cite
|
Sign up to set email alerts
|

What do your customers think about? To guess or to know?

Abstract: The customer is central to any company's activity. Although this is the fundamental truth, many companies turn their attention to the customer only when sales decrease. This article tells how to prevent the negative changes. This article will not reveal the communication strategy elements for interacting with customers, neither will it consider building the necessary IT infrastructure for its implementation, it will rather address the basics of developing approaches to interacting with different types of custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The customer-centric approach is a component of corporate culture, and in the new generation of system standards, the customer organization's customer-centricity is emphasized (Samuel, Rajesh, Rajanna & Franklin, 2021). There are different types of customers: new and unchanging, random and loyal, potential and followers, and each type of customer contributes differently to total revenue, but they are all equally important (Linde & Philippov, 2021). Quality Function Deployment (QFD) is the systematization of listening to the "voice of the customer" and translating customer needs through each stage of product development into products that meet customer requirements is a necessary condition; through QFD, We analyze customers' needs, make technical responses, make the supply sequence to the market the priority, train professionals in their respective positions, and improve the quality of human resources (Pandya, Ismoyowati & Suharno, S., 2020).…”
Section: Marketing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The customer-centric approach is a component of corporate culture, and in the new generation of system standards, the customer organization's customer-centricity is emphasized (Samuel, Rajesh, Rajanna & Franklin, 2021). There are different types of customers: new and unchanging, random and loyal, potential and followers, and each type of customer contributes differently to total revenue, but they are all equally important (Linde & Philippov, 2021). Quality Function Deployment (QFD) is the systematization of listening to the "voice of the customer" and translating customer needs through each stage of product development into products that meet customer requirements is a necessary condition; through QFD, We analyze customers' needs, make technical responses, make the supply sequence to the market the priority, train professionals in their respective positions, and improve the quality of human resources (Pandya, Ismoyowati & Suharno, S., 2020).…”
Section: Marketing Managementmentioning
confidence: 99%
“…To improve the quality of product features or specific services (Linde & Philippov, 2021;Attaqwa, Saputra & Khamal, 2021). The Just in Time (JIT) supply chain has attracted increasing interest from operations management scholars (Tseng, Wee, Reong & Wu, 2019;Chung, Talluri, Kovács, 2018;Yao & Hsu, 2018).…”
Section: Marketing Managementmentioning
confidence: 99%
“…ChatGPT experiences over a billion monthly visits and is increasingly utilized in medical contexts [2]. One survey reports more than 80% of US respondents had used a chatbot in 2023, and another suggests that despite prohibitions on medical use by vendors, millions of medical queries are submitted on a weekly basis by users of OpenAI alone [3,4]. Such publicly available large language models (LLMs) like ChatGPT can be a promising source of healthcare information.…”
Section: Introductionmentioning
confidence: 99%
“…Beside those benefits for the businesses, it is much more important whether the consumers' attitudes and intention to use chatbots. The studies show that consumers except Generation Z and Millennials, may show reluctance to communicate with a chatbot, instead they may prefer to wait for a human agent in a service queue (Chatbots Magazine, 2019;Userlike, 2020). On the other side, a study analyzing Y and Z generations' attitudes toward chatbot revealed that the consumers' experiences with chatbots might be problematic and unsatisfying to solve their problems (Seyitoğlu, 2019).…”
Section: Introductionmentioning
confidence: 99%